A new and accessible instrumentation to determine urea in UHT milk using digital image analysis. (1st July 2022) - Honorato Santos Neto, João; dos Santos, Liz Oliveira; dos Santos, Ana Maria Pinto; Galvão Novaes, Cleber; Luis Costa Ferreira, Sergio
Graphical abstract: Highlights: A new method based on digital image analysis was applied to determine urea in UHT milk. The digital image acquisition apparatus was built with PVC tubes and other low-cost materials. The method presents itself as an efficient alternative to the FT-IR technique to determine urea. Digital image analysis proved to be a promising technique to assess adulteration and milk quality. Abstract: This research demonstrates the development, optimization and application of a new low-cost detection system, based on digital image analysis, for the detection of urea in ultra-high-temperature (UHT) milk samples. The apparatus built in the laboratory, allows the capture of images through a simple system built by polyvinyl chloride (PVC) tubes, a digital microscope and a peristaltic mini-pump, after the colorimetric reaction between urea and diacetylmonoxime (butane-2, 3-dionammonoxime). The red, green and blue (RGB) and hue, saturation and value (HSV) color systems were studied, with the saturation channel of the HSV color system selected as the analytical signal. Subsequently, the experimental chemical conditions were evaluated through multivariate experimental designs and the optimal conditions were defined. The proposed method was validated, and the detection and quantification limits presented by the method were 0.35 mg L −1 and 0.52 mg L −1, respectively; precision, ranged between 1.6  and 2.8 %. The results were compared with those obtained using the mid-infrared technique and no statistically significant differences were observed at a 95 % confidence level. The proposed method was applied to eight UHT milk samples that presented urea content ranging from 187 to 386 mg L −1 . The mean values obtained are in agreement with values presented in other studies for the determination of urea in milk. The results indicated that the system described and validated here is promising and can be applied to assess the authenticity and quality of milk.